Heterochromatic knobs gene-like effects on flowering time, and the seed aging epigenetic-genetic program in maize - Carvalho, Renata Flávia de (2020)
Maize (Zea mays spp. mays) is a cultivated species known for its wide genetic variability. A large part of the diversity observed in the genome size is due to the presence of repetitive sequences, which can compose up to 90% of DNA in a species. In particular, knobs are regions of constitutive heterochromatin present in the maize genome and due to their repetitive nature, no specific function has been assigned until this moment. Because it is a cytological region visibly observed under a microscope, knobs give the maize genome a unique karyotype variability. Despite no assigned role, there is evidence of a possible influence of the knobs on maize phenotypic traits. Seed aging is an equally relevant area, as it can subsidize seed storage practices, which are essential for the conservation of genetic resources, including the maize crop. There is a relationship between seed aging and the impact on crop yield and this has been demonstrated through cytogenetic and physiological studies. However, a deeper understanding of the consequences of aging on the plants epigenome remains unclear. In this context, the two chapters of this thesis are structured, which have very different objectives, but which are complementary with regard to the scientific contribution to the areas of genetics and maize breeding. The first chapter discussed the hypotheses of the heterochromatic knobs contribution to the genome size and maize flowering time. In this study, maize inbred line families (JD 1-3, JD 2-1 and JD 4-4) and the hybrids obtained between them were used. They were mapped to the knobs in specific positions on chromosomes 3, 5, 7 and 9. All of this material was characterized in terms of male and female flowering time and genome size. The data were analysed using an adaptation of the Genome-Wide Association Study (GWAS), where knobs were used in place of molecular markers of single nucleotide polymorphism (SNPs). These analyses showed a significant association between the knob on the short arm of chromosome 9 and the flowering time, in which the knob presence in homozygosity or heterozygosis on chromosome 9 can lead to a reduction in the maize flowering time, making it earlier. The second chapter aimed to evaluate the effects of natural seed aging and its impacts on germination, behaviour of chromosomes and maize chromatin. In this study, genotypes of the JD 4-1 inbred line family were used, which were kept stored for 24 years in a cold chamber. Aged and non-aged seeds were analysed comparatively for the parameters of mitotic index, chromosomal changes, germination percentage, meiotic analysis and DNA methylation. There were significant differences between treatments for all parameters analysed. The most expressive result was observed in the methylation level, in which the aged seeds presented higher DNA methylation values than the non-aged seeds. Among the aged seeds, there were also differences in methylation, showing that there is a genotype-specific response to aging. The combined action between the genetic background and epigenetic indexing contributed to maintaining the aged seeds viability after long years of storage.